KEBIJAKAN BELT AND ROAD INITIATIVE SEBAGAI ALAT SOFT POWER CINA DALAM MEMBANGUN HEGEMONI DI KAWASAN ASIA TENGGARA (STUDI KASUS: INVESTASI CINA DI INDONESIA) - Gerald Theodorus Lumban Toruan (Jurnal Soshum Insentif, 2021)
Abstract - China is currently in an effort to build a new power in the world, through the Chinese Belt and Road Initiative in the era of President Xi Jinping, providing investment assistance to Southeast Asian countries. This investment is given in order to build Chinese hegemony in Southeast Asia. One of the countries in Southeast Asia that is co-financed by China is Indonesia, by prioritizing Indonesia's national interests in cooperation with China in infrastructure development in Indonesia. This research used qualitative methode research with a case study approach, while the data collected through literature study. The final conclusion of this research is that China's BRI program in Indonesia must continue to prioritize national interests and also the sovereignty of the Indonesian state, Indonesia should not be sold like the country of Sri Lanka. Abstrak - Cina saat ini sedang dalam upaya membangun kekuatan baru di dunia, melalui kebijakan Belt and Road Initiative Cina di era Presiden Xi Jinping banyak memberikan bantuan investasi ke negara-negara Asia Tenggara. Pemberiaan investasi ini dalam rangka membangun hegemoni Cina di kawasan Asia Tenggara. Indonesia adalah salah satu negara di Asia Tenggara yang ikut dibiayai Cina dengan mengedepankan kepentingan nasional Indonesia bekerjasama dengan Cina dalam pembangunan infrastruktur di Indonesia. Penelitian yang digunakan adalah penelitian kualitatif dengan pendekatan studi kasus, adapun penulis mengumpulkan data melalui studi pustaka. Kesimpulan dari penelitian ini adalah program BRI Cina di Indonesia haruslah tetap mengedepankan kepentingan nasional dan juga kedaulatan negara Indonesia, Indonesia jangan sampai terjual seperti negara Srilanka.